Antibacterial activity of sophorolipids produced by candida bombicola on Gram-positive and Gram-negative bacteria isolated from salted hides - (:unkn) unknown (American Leather Chemists Association, 2016)
Salted hides and soaked hides treated with certain antibacterial agents, may still contain different proteolytic and lipolytic Gram-positive and Gram-negative bacteria that affect the quality of leather adversely. The prevalence of bacteria resistant to antimicrobial agents in the leather industry has drawn attention of scientists to search new and effective antimicrobial agents. Examination of antimicrobial glycolipids such as sophorolipids for their effectiveness against proteolytic and lipolytic hide- degrading microorganisms, may offer important information. Hence, we describe a research that evaluates the susceptibility of various hide-degrading bacteria to sophorolipids. These extracellular glycolipids were produced by fermentation using Candida bombicola ATCC 22214. Palmitic acid, stearic acid, and oleic acid were used respectively to produce SL-p, SL-s, and SL-o. The minimal inhibitory concentrations (MICs) of SL-p, SL-s, and SL-o against Gram-positive endospore-forming bacteria (Bacillus licheniformis, B. pumilus and B. mycoides), Gram-positive bacteria (Enterococcus faecium, Aerococcus viridans, Staphylococcus xylosus, S. cohnii and S. equorum), Gram-negative bacteria {Pseudomonas luteola, Enterobacter cloacae, E. sakazakii and Vibrio fluvialis), and mixed culture of these isolates were examined using an agar dilution method. The MICs of both SL-p and SL-o against the test bacteria were determined as 19.5 |ig/mL, with an exception that E. cloacae was inhibited by SL-o at a MIC of 9.76 Hg/mL. Although MICs of SL-p did not change against the test bacteria, the MICs of SL-s (ranging from 4.88 (ig/mL to 19.5 (ag/ mL) changed according to species of the test bacteria. The lowest MICs of SL-s were found to be 4.88 ng/mL against B. licheniformis, B. pumilus, P. luteola, S. xylosus and B. mycoides. The MICs of SL-p, SL-s, and SL-o against the mixed bacterial culture were detected as the same (19.5 ng/mL). In conclusion, SL-p, SL-s, and SL-o inhibited the growth of 12 different hide bacteria and their mixed culture, and have broad-spectrum activity. The results obtained in the present study may be valuable for the development of SL-p, SL-s, and SL-o as antimicrobial surfactants in the preservation and soaking processes of hides and skins.